Pemanfaatan Ampas Tebu Dan Kulit Pisang Kepok Sebagai Karbon Aktif Pada Proses Adsorpsi Untuk Menyisihkan Kadar Fe dan Mn - Addzikri, Ahmad Iqbal; Rosariawari, Firra (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The increasing problem of water pollution due to high levels of heavy metals which are often found in well water in various regions affects water quality which can have a negative impact on public health and the environment. Therefore, an effective solution is needed to reduce this contamination. One promising solution is the use of activated carbon derived from organic materials, such as sugarcane bagasse and kepok banana peel. This research aims to analyze the optimal dose and effectiveness of activated carbon produced from sugar cane bagasse and kepok banana peel which is activated with 5% H₃PO₄ in the adsorption process to reduce iron (Fe) and manganese (Mn) levels in well water. The research was carried out with varying doses of activated carbon of 4 grams, 6 grams, and 8 grams, as well as varying contact times of 20, 30, 40, 50, and 60 minutes. The results of the research show that activated carbon from sugar cane bagasse and kepok banana peel has a significant ability to remove these two heavy metals with varying effectiveness. The results of this research provide a sustainable and environmentally friendly alternative for water treatment and open up opportunities for utilizing organic waste as raw materials in water treatment methods that can improve the quality of contaminated well water.